2023
DOI: 10.1155/2023/3523592
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Control Technology of Rockburst Induced by Thick Hard Roof and Residual Coal Pillar: A Case Study

Abstract: Rockburst caused by the fracture of thick hard roof and the instantaneous instability of residual coal pillar seriously jeopardize the deep coal mining safety. This study takes Boertai Coal Mine, Shendong, China, as the engineering background, in which dynamic instability mechanisms of the gob-side roadway surrounding rock are analyzed by integrating field research, theoretical analysis, and numerical simulation. The results show that the overlying residual coal pillar, side abutment pressures, and front abutm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, DHF can be used to control the propagation direction of hydraulic fractures by grooving specified rock formations [36]. Another method is to construct directional drilling according to the position of hard rock and then use hydraulic fracturing [40,46,47]. In future studies, the directional hydraulic fracturing scheme for roofs above residual coal pillars should be studied, and the control effect of HF and DHF on strong mining pressures should be comparatively analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DHF can be used to control the propagation direction of hydraulic fractures by grooving specified rock formations [36]. Another method is to construct directional drilling according to the position of hard rock and then use hydraulic fracturing [40,46,47]. In future studies, the directional hydraulic fracturing scheme for roofs above residual coal pillars should be studied, and the control effect of HF and DHF on strong mining pressures should be comparatively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [39] concluded that roof cutting with a vertical hydraulic fracture at a specified position, also known as fixed-length roof cutting, can reduce the support load and keep the immediate roof intact. Liu et al [40] proposed a directional hydraulic fracturing roof-cutting technology for controlled rock bursts induced by thick, hard roofs and residual coal pillars under repeated mining in close coal seam groups. Gao et al [41] presented a method for subjecting hard roofs to ground fracturing in the Datong mining area in China, and physical simulations were used to study the control effect of ground fracturing on strata structure and energy release.…”
Section: Introductionmentioning
confidence: 99%
“…18 Liu et al analyzed the mechanism of rock burst induced by a thick and hard roof and residual coal pillars through field investigations, theoretical analysis, and numerical simulations based on the engineering background of the Shendong Buertai Coal Mine. 19 Regarding research on rock burst prevention and control methods, Gao et al studied the seismic isolation technology and implementation method of a deep rock burst roadway and effectively protected the stability of the structure of the rock surrounding the roadway through dual protection means of isolation and shock absorption. 20 Xu et al studied the dynamic response characteristics of the surrounding rock and support system of a roadway under different vibration intensities and proposed the full anchor cable yield support technology, which effectively controls the stability of the rock surrounding the roadway under dynamic rock burst.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied triangular coal mining technology and roof control technology for the problem of coal resource waste caused by coal pillar areas with irregular boundaries and triangular coal pillars . Liu et al analyzed the mechanism of rock burst induced by a thick and hard roof and residual coal pillars through field investigations, theoretical analysis, and numerical simulations based on the engineering background of the Shendong Buertai Coal Mine . Regarding research on rock burst prevention and control methods, Gao et al studied the seismic isolation technology and implementation method of a deep rock burst roadway and effectively protected the stability of the structure of the rock surrounding the roadway through dual protection means of isolation and shock absorption .…”
Section: Introductionmentioning
confidence: 99%
“…In the process of multi-coal seam mining, after the upper coal seam is mined, a large amount of coal pillars are often left behind [1]. When the lower coal seam mining face advances into the influence range of the mining area, the roof structure collapses again, and the thick and hard suspended roof breaks and fails under the additional stress of the residual coal pillar [2]. The special coal-rock occurrence conditions and repeated mining disturbance cause abnormal mine pressure, and there is a hidden danger of cutting the roof pressure on the hydraulic support of the mining face.…”
Section: Introductionmentioning
confidence: 99%